Digital music consumption on the internet - Luis Aguiar; Bertin Martens (European Commission, Joint Research Centre (JRC), 2013)
The goal of this paper is to analyze the behaviour of digital music consumers on the Internet. Using clickstream data on a panel of more than 16,000 European consumers, we estimate the effects of illegal downloading and legal streaming on the legal purchases of digital music. Our results suggest that Internet users do not view illegal downloading as a substitute to legal digital music. Although positive and significant, our estimated elasticities are essentially zero: a 10% increase in clicks on illegal downloading websites leads to a 0.2% increase in clicks on legal purchases websites. Online music streaming services are found to have a somewhat larger (but still small) effect on the purchases of digital sound recordings, suggesting complementarities between these two modes of music consumption. According to our results, a 10% increase in clicks on legal streaming websites lead to up to a 0.7% increase in clicks on legal digital purchases websites. We find important cross country difference in these effects.
Keywords: K42; L82; L86; Z1; 330; Digital Music; Copyright; Downloading; Streaming; Piracy on the internet